The Effect of Zone 3 Physical Activity on Relax Heart Rate and Peak Flow Rate - Sulaeman Sulaeman; Hasyim Hasyim (STKIP Muhammadiyah Kuningan, 2022)
The problem raised in this study is whether zone 3 physical activity affects peak flow rate and relaxed heart rate in FIK UNM students. At the same time, this study aimed to determine the effect of zone 3 physical activity on peak flow rate and relaxed heart rate in FIK UNM students. The type of research used is experimental research. The number of samples used as many as ten samples of students with a sampling technique using the purposive sampling method. Data collection techniques using peak flow rate test and heart rate test. The analysis technique used is descriptive analysis, normality test and paired sample test or influence test. From the data processing results on the effect of zone 3 physical activity on the Peak flow rate, a significant value of 0.001 was obtained, which was smaller than 0.05. So, zone 3 physical activity substantially affects the peak flow rate in FIK UNM students. Furthermore, it is known that the average peak flow rate before being given treatment is 416,000. This value has increased after being given treatment that is equal to 441,000. This indicates that the value of the vital lung capacity of students experienced a positive change. The results of data processing the effect of zone 3 physical activity, an open heart rate obtained a significant value of 0.000, more diminutive than 0.05. So, zone 3 physical activity has a significant effect on the available heart rate in FIK UNM students. Furthermore, it is known that the average value of open-heart rate before being given treatment is 86.2000. This value decreased after being given 80.2000 treatment. This indicates that the open heart rate of students also experienced a positive change.